2020
DOI: 10.1111/vco.12626
|View full text |Cite
|
Sign up to set email alerts
|

miR‐497 induces apoptosis by the IRAK2/NF‐κB axis in the canine mammary tumour

Abstract: Since companion dogs have the same living environment as humans, they are a good animal model for the study of human diseases; this is especially true of canine spontaneous mammary tumours models. A better understanding of the natural history and molecular mechanisms of canine mammary tumour is of great significance in comparative medicine. Here, we collected canine mammary tumour cases and then assayed the clinical cases by pathological examination and classification by HE staining and IHC. miRNA‐497 family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…57,105 NF-kB signaling is essential in maintaining a normal immune response and long-term use of an NF-kB inhibitor could theoretically result in immunodeficiency. 52,106 In addition, NF-kB inhibitors could inhibit T cells that recognize and kill tumor cells, potentially worsening disease. Although the broad role of NF-kB and cell type-specific action complicate its potential as an anticancer target, 82 there are several examples of NF-kB inhibitors that have shown promise in canine medicine.…”
Section: Nf-kb Inhibition As a Treatment For Canine Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…57,105 NF-kB signaling is essential in maintaining a normal immune response and long-term use of an NF-kB inhibitor could theoretically result in immunodeficiency. 52,106 In addition, NF-kB inhibitors could inhibit T cells that recognize and kill tumor cells, potentially worsening disease. Although the broad role of NF-kB and cell type-specific action complicate its potential as an anticancer target, 82 there are several examples of NF-kB inhibitors that have shown promise in canine medicine.…”
Section: Nf-kb Inhibition As a Treatment For Canine Cancersmentioning
confidence: 99%
“…60 Others reported relative miR-497 downregulation in canine mammary cancer tissue and discovered that restoration of miR-497 inhibited active NF-kB signaling in vitro. 106 Protein phosphatase 2A (PP2A) is an evolutionarily conserved serine/threonine protein phosphatase that functions as a tumor suppressor that can be inhibited by SET; increased SET protein levels in canine mammary cancer and osteosarcoma suppresses PP2A activity, which in turn enchances mTOR, B-catenin, and NF-kB signaling in these cancers. 38,86 Overexpression of the secreted frizzled protein 2 (sFRP2) in canine mammary tumor cells has been documented as key to resistance to apoptosis.…”
Section: Mammary Cancermentioning
confidence: 99%
“…Lutful et al using a quantitative polymerase chain reaction strategy in cell lines from female dogs diagnosed with spontaneous mammary carcinomas or adenocarcinomas, demonstrated that miR-141 is a strong oncomiR, belonging to the miR-200 family [ 61 ]. Significant levels of miR-141 expression are strongly associated with highly aggressive breast carcinomas (grade III) compared to grade II breast cancer [ 73 ].…”
Section: Biomarkers Of Tnbc and Cmts: Current Biomarkers And Potentia...mentioning
confidence: 99%